The HSP90 Inhibitor Ganetespib Alleviates Disease Progression and Augments Intermittent Cyclophosphamide Therapy in the MRL/lpr Mouse Model of Systemic Lupus Erythematosus. - Yuan Liu; Josephine Ye; Luisa Shin Ogawa; Takayo Inoue; Qin Huang; John Chu; Richard C Bates; Weiwen Ying; Andrew J Sonderfan; Patricia E Rao; Dan Zhou (PLoS ONE, 2015)
Systemic lupus erythematosus (SLE) is a complex, systemic autoimmune disease with a diverse range of immunological and clinical manifestations. The introduction of broad spectrum immunosuppressive therapies and better management of acute disease exacerbations have improved outcomes for lupus patients over recent years. However, these regimens are burdened by substantial toxicities and confer significantly higher risks of infection, thus there remains a significant and unmet medical need for alternative treatment options, particularly those with improved safety profiles. Heat shock protein 90 (HSP90) is a ubiquitously expressed molecular chaperone that acts as an important modulator of multiple innate and adaptive inflammatory processes. Of note, accumulating clinical and experimental evidence has implicated a role for HSP90 in the pathogenesis of SLE. Here we evaluated the potential of HSP90 as a therapeutic target for this disease using the selective small molecule inhibitor ganetespib in the well-characterized MRL/lpr autoimmune mouse model. In both the prophylactic and therapeutic dosing settings, ganetespib treatment promoted dramatic symptomatic improvements in multiple disease parameters, including suppression of autoantibody production and the preservation of renal tissue integrity and function. In addition, ganetespib exerted profound inhibitory effects on disease-related lymphadenopathy and splenomegaly, and reduced pathogenic T and B cell lineage populations in the spleen. Ganetespib monotherapy was found to be equally efficacious and tolerable when compared to an effective weekly dosing regimen of the standard-of-care immunosuppressive agent cyclophosphamide. Importantly, co-treatment of ganetespib with a sub-optimal, intermittent dosing schedule of cyclophosphamide resulted in superior therapeutic indices and maximal disease control. These findings highlight the potential of HSP90 inhibition as an alternative, and potentially complementary, strategy for therapeutic intervention in SLE. Such approaches may have important implications for disease management, particularly for limiting or preventing treatment-related toxicities, a major confounding factor in current SLE therapy.